Systematic mapping of experimental approaches to studying common mycorrhizal networks in arbuscular mycorrhiza - Anika Lehmann; Matthias C. Rillig (Plants, People, Planet)
Societal Impact Statement Common mycorrhizal networks (CMN) capture the imagination of researchers and the public alike and have played a large role in communicating about mycorrhiza in general. With many of the claims about the functional importance of CMN recently under intense scrutiny, it becomes important to assess the literature on this topic. We systematically map experimental approaches, uncovering large data gaps, with evidence from field studies and data on ecosystem processes lacking. Very few studies meet the strictest recommended criteria, limiting our understanding of CMN‐mediated effects on plants and soils. A renewed research effort needs to unravel the contribution of CMNs under global environmental change. Summary Common mycorrhizal networks (CMN) are a research area within mycorrhizal ecology, studying the effects of mycorrhizal fungi linking plant roots. Experimentally studying the functioning of such networks is challenging because of the presence of many different types of network links that give rise to potentially confounding effects. Here, we collect, collate, and describe the research evidence for common mycorrhizal networks, specifically for arbuscular mycorrhiza (AM), using a systematic mapping approach. We find that not all studies tested networks formed exclusively by AM fungi, but that other filamentous fungi were present and that very few articles report on experiments fulfilling the current stringent definition (demanding hyphal continuity between plant roots). Furthermore, most research is limited to controlled environmental conditions with certain plant, fungal, and resource‐transfer variables measured, while microbial community responses or ecosystem processes are neglected. Given the broad interest in this topic, we see a need to strengthen the evidence base on “common mycorrhizal networks” in AM fungi, necessitating a renewed research effort focusing on a range of levels of mechanistic resolution (from simple to complex networks with and without hyphal continuity). Additionally, neglected experimental situations (e.g., field studies in general) and microbial community or ecosystem‐level responses should be included in future research.